KAJIAN KRIMINOLOGI TERHADAP PENANGGULANGAN KASUS PENYELUNDUPAN NARKOBA YANG DIDOMINASI MELALUI PERAIRAN SELAT MALAKA - Zega, Yuliana Silvy Rosadi; Radin, Martina; Fitriono, Riska Andi (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
Based on Law No. 35 of 2009 on Drugs Article 113 paragraphs 1 and 2, drug smuggling have long be known as a crime. Indonesia belongs to the one of the target countries with the largest drug market commodity in the Southeast Asia region. The drug trafficking situation in Indonesia is also influenced by the ease of accessibility of circulation by utilizing land and sea routes, especially dominated through the Strait of Malacca.The existence of that activity still occurs. This study seeks to examine what is the factors which make the drug smuggling activities through the Strait of Malacca never completed and how the law works and efforts that have so far been made by the competent authorities to prevent drug transactions by sea. This research uses normative research methods by conducting case studies (case approaches). The results showed that there are two main factors that make drug smuggling activities dominated through the Strait of Malacca due to the strait area as an international transaction route that allows the entry of illegal foreign vessels and the second one, its because the lack of supervision by the authorities due to policy overlap so that the synergy of supervision does not run optimally.